Sliding mode combined with PI controller applied for current control of grid-connected single-phase inverter under distorted voltage conditions - Lucas D. Augusto; Luís F. N. Lourenço; José A. T. Altuna; Alfeu J. Sguarezi Filho (Eletrônica de Potência)
Grid-connected inverters must be synchronized with the electrical grid to ensure stability and efficiency. However, abrupt grid distortions and harmonic components can degrade the controller’s performance. This paper proposes a sliding mode controller combined with a PI controller for current control in a single-phase grid-connected inverter to enhance Total Harmonic Distortion performance. The primary contribution of this work is the development of a nonlinear controller with a constant switching frequency, addressing the common chattering problem in sliding mode controllers while maintaining adequate performance under distorted voltage conditions using a Phase-Locked Loop. The controller's performance was evaluated through laboratory experiments under normal and distorted grid conditions, and the results were compared with a repetitive controller, demonstrating its effectiveness in suppressing harmonics in regular operation and under distorted grid voltage conditions.